Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1074/jbc.m603500200
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Adenylyl Cyclase Mediates Nerve Growth Factor-induced Activation of Rap1

Abstract: Nerve growth factor (NGF) and the ubiquitous second messenger cyclic AMP (cAMP) are both implicated in neuronal differentiation. Multiple studies indicate that NGF signals to at least a subset of its targets via cAMP, but the link between NGF and cAMP has remained elusive. Here, we have described the use of small molecule inhibitors to differentiate between the two known sources of cAMP in mammalian cells, bicarbonate-and calcium-responsive soluble adenylyl cyclase (sAC) and G protein-regulated transmembrane a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
90
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 46 publications
4
90
1
Order By: Relevance
“…Interestingly, it has been suggested that Trk and p75 NTR may act either as subunits of a single receptor complex or as independent transducers of distinct neurotrophin functions (Chao, 1994). Although it is generally thought that the NGF-induced activation of Rap1, which we have shown to be mediated via sAC (Stessin et al, 2006), involves TrkA, rather than p75 NTR , we have also found sAC to mediate the activation of Rap1 by TNF in neutrophils (Han et al, 2005). Thus, the roles of TrkA and p75 NTR in the activation of sAC by NGF are a subject for future studies.…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…Interestingly, it has been suggested that Trk and p75 NTR may act either as subunits of a single receptor complex or as independent transducers of distinct neurotrophin functions (Chao, 1994). Although it is generally thought that the NGF-induced activation of Rap1, which we have shown to be mediated via sAC (Stessin et al, 2006), involves TrkA, rather than p75 NTR , we have also found sAC to mediate the activation of Rap1 by TNF in neutrophils (Han et al, 2005). Thus, the roles of TrkA and p75 NTR in the activation of sAC by NGF are a subject for future studies.…”
mentioning
confidence: 62%
“…Application of a reagent such as the tmAC-specific activator forskolin yields very large changes in whole-cell cAMP, which may have little physiological relevance to a particular biological process. In contrast, the microdomain model of cAMP action dictates that subtle changes in whole-cell cAMP, as can be observed when using bicarbonate to stimulate endogenous sAC activity in an in vitro assay or during NGF treatment of PC12 cells (Stessin et al, 2006), can have profound physiological consequences. In the future, great care should be exercised when using pharmacological agents that alter cAMP.…”
mentioning
confidence: 99%
See 3 more Smart Citations